2022
DOI: 10.1155/2022/2221618
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Care-Seeking Behavior for Common Childhood Illnesses and Its Predictors in Ethiopia: Meta-Analysis

Abstract: Background. Healthcare-seeking interventions can potentially reduce child mortality; however, many children die in developing countries without reaching a health facility. The World Health Organization reported that 70% of child deaths are related to delay care-seeking. So, this review is aimed at identifying mothers’ care-seeking behavior for common childhood illnesses and predictors in Ethiopia. Methods. Systematic search of studies was done on PubMed, Scopus, Web of Science, institutional repositories, Acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Children living in wealthier households, from the South–South geopolitical zone and whose mother had at least secondary education were more likely to be taken for care than those in poorer households, other geopolitical zones, or less educated mothers ( 10 ). Previous studies from low- and middle-income countries globally have also identified child sex and age ( 11 , 12 ), maternal education and marital status ( 13–15 ), household dynamics and wealth index ( 11 , 15 , 16 ), perceived illness severity and trust in health care ( 12 ) as determinants of care seeking for sick under-five children. However, these relationships can differ by setting, highlighting the importance of local empirical studies on care seeking for children under-five to guide interventions design and prioritization for child health programming ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Children living in wealthier households, from the South–South geopolitical zone and whose mother had at least secondary education were more likely to be taken for care than those in poorer households, other geopolitical zones, or less educated mothers ( 10 ). Previous studies from low- and middle-income countries globally have also identified child sex and age ( 11 , 12 ), maternal education and marital status ( 13–15 ), household dynamics and wealth index ( 11 , 15 , 16 ), perceived illness severity and trust in health care ( 12 ) as determinants of care seeking for sick under-five children. However, these relationships can differ by setting, highlighting the importance of local empirical studies on care seeking for children under-five to guide interventions design and prioritization for child health programming ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the body of literature which has investigated willingness to pay amongst those targeted by the SHI, information on healthcare seeking behavior (HSB) for formal sector employees is limited [25]. The existing literature tends to focus on healthcare seeking behavior for children or for specific diseases such as HIV/AIDS and Tuberculosis [26][27][28][29]. Information on the HSB of formal sector employees is needed to shed light on the potential challenges that current patterns of HSB may create for the implementation of the SHI.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the body of literature which has investigated willingness to pay amongst those targeted by the SHI, information on health-seeking behaviour (HSB) for formal sector employees is limited [22]. The existing literature tends to focus on healthcare seeking behavior for children or for specific diseases such as HIV/AIDS and Tuberculosis [23][24][25][26]. Information on the HSB of formal sector employees is needed to shed light on the potential challenges that current patterns of HSB may create for the implementation of the SHI.…”
Section: Introductionmentioning
confidence: 99%